2019
DOI: 10.1111/exd.13934
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid treats acne vulgaris by suppressing AMPK/SREBP1 pathway in sebocytes

Abstract: Acne vulgaris is a prevalent cutaneous disease characterized by a multifactorial pathogenic process including hyperseborrhea, inflammation, over‐keratinization of follicular keratinocytes and Propionibacterium acnes (P acnes) overgrowth. Salicylic acid (SA), a beta‐hydroxy acid, is frequently used in the treatment of acne. SA has been found to decrease skin lipids and to possess anti‐inflammatory properties. However, few studies have elucidated the mechanisms and pathways involved in such treatment of acne. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Shabnam et al suggested that activation of AMPK regulated steroidogenesis in granulosa cells from PCOS rats [40]. Moreover, growing evidence demonstrated that SREBP1, as a downstream molecule, regulated by AMPK [41][42][43]. In this study, we found that EA intervention facilitated the activation of AMPK pathway in PCOS-like rats.…”
Section: Discussionsupporting
confidence: 58%
“…Shabnam et al suggested that activation of AMPK regulated steroidogenesis in granulosa cells from PCOS rats [40]. Moreover, growing evidence demonstrated that SREBP1, as a downstream molecule, regulated by AMPK [41][42][43]. In this study, we found that EA intervention facilitated the activation of AMPK pathway in PCOS-like rats.…”
Section: Discussionsupporting
confidence: 58%
“…SA at a 30% concentration is a naturally active ingredient with anti-inflammatory and keratin-exfoliating properties, which has been widely used in skin diseases, particularly in acne vulgaris (21). SA decreases sebum secretion through downregulation of the adenosine monophosphate-activated protein kinase/sterol regulatory element-binding protein-1 signaling pathway, and antagonizes the inflammatory response through inhibition of the NF-κB signaling pathway (22). In addition, SA at 20-30% concentration can disrupt intercorneocyte cohesion, causing a rapid differentiation of keratinocytes and peeling the entire epidermis, resulting in the reorganization of the epidermis and the removal of excess melanin (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism by which SA acts in PPR is not clear, two factors are hypothesized to support its functional mechanism. First, SSA 30% can inhibit inflammation via the NF-κB signaling pathway and inhibit interleukin-1β and tumor necrosis factor involved in rosacea (12,22). Second, the chemical exfoliation and whitening effect of SSA 30% facilitate the reorganization of the epidermis and prevent pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…[81] In fact, the last two years have seen an impressive phalanx of rodent model-based SG papers. Together with the fact that one now can make use of a rich tools box of human sebocyte cell culture models, [32,78,82,83] and fertilized by increasing insights into the lipid biology, [84] neuroendocrinology and neuropharmacology of human SGs, [85,86] this has made the SG the second-best studied of all skin appendages. Combined with the clinical relevance of the SG in the ongoing acne pathobiology debate, which is getting ever more intriguing, [10,84,[87][88][89] The regulatory function of Gata6 seems to extend to the sebaceous duct and the hair canal in murine skin, as reported by Swanson et al.…”
Section: Epithelial-to-mesenchymal Stem Cell Transition In a Humanmentioning
confidence: 99%